Role of the cation-chloride-cotransporters in the circadian system - Shihan Salihu (Elsevier, 2021)
The circadian system plays an immense role in controlling physiological processes in our body. The suprachiasmatic nucleus (SCN) supervises this system, regulating and harmonising the circadian rhythms in our body. Most neurons present in the SCN are GABAergic neurons. Although GABA is considered the main inhibitory neurotransmitter of the CNS, recent studies have shown that excitatory responses were recorded in this area. These responses are enabled by an increase in intracellular chloride ions [Cl−]i levels. The chloride (Cl−) levels in GABAergic neurons are controlled by two solute carrier 12 (SLC12) cation-chloride-cotransporters (CCCs): Na+/K+/Cl− co-transporter (NKCC1) and K+/Cl− co-transporter (KCC2), that respectively cause an influx and efflux of Cl−. Recent works have found altered expression and/or activity of either of these co-transporters in SCN neurons and have been associated with circadian rhythms. In this review, we summarize and discuss the role of CCCs in circadian rhythms, and highlight these recent advances which attest to CCC's growing potential as strong research and therapeutic targets.